Aktivitas Public Relations Hotel Harper by Aston melalui Media Sosial di Masa Pandemi - Syifa Almyra; M Subur Drajat (Bandung Conference Series: Public Relations, 2022)
Abstract. Since the outbreak of the corona virus outbreak, people are advised to stay at home and avoid traveling for anything that is not important. In times of crisis like this, Hotel X Purwakarta by Y has had a very significant impact, such as reduced visitor arrivals, reduced meeting activities at X Hotel and reduced employees. Seeing conditions that are very competitive every day it is increasingly difficult, so it requires a Public Relations in optimizing his duties. As well as assisting several activities that can attract customers' interest in the midst of a pandemic through social media. The purpose of this study was to determine the communication activities of X's hotel public relations through social media during the pandemic. The research methodology is qualitative with a case study approach. The paradigm used by Constructivism. Data collection techniques through online and offline interviews, field observations and documentation. The results of this study found that Public Relations communication activities by inviting journalists via Zoom Meeting, holding greetings with hotel guests and disseminating information via Instagram. Public Relations activities by providing free staycations to selected people or agencies (Influencers) and cross-marketing with several parties through tags on social media. The reason for using social media as a marketing strategy is because social media has the power to influence public opinion and create a positive/negative image of the parties it reports on and the great role of social media for the sustainability of an institution. Abstrak. Semenjak merebaknya wabah virus corona, masyarakat diimbau untuk tetap di rumah dan menghindari bepergian untuk sesuatu yang tidak penting. Pada saat kondisi krisis seperti ini, Hotel X Purwakarta by Y memperoleh dampak yang sangat signifikan seperti berkurangnya kedatangan pengunjung, kegiatan rapat yang sering dilaksanakan di Hotel X menjadi berkurang dan pengurangan karyawan. Melihat kondisi yang sangat kompetitif setiap harinya dirasa semakin sulit, sehingga memerlukan seorang Public Relations dalam mengoptimalisasikan tugasnya. Serta membantu beberapa aktivitas yang dapat menarik minat pelanggan ditengah pandemi melalui media sosial. Tujuan dari penelitian ini untuk mengetahui aktivitas komunikasi public relations hotel X melalui media social dimasa pandemic. Metodologi penelitian ini adalah Kualitatif dengan pendekatan studi kasus. Paradigma yang digunakan Konstruktivisme. Teknik pengumpulan data melalui wawancara online dan offline, observasi lapangan dan dokumentasi. Hasil penelitian ini ditemukan bahwa aktivitas komunikasi Public Relations dengan mengundang para wartawan via Zoom Meeting, mengadakan greeting dengan para tamu hotel serta penyebaran informasi melalui Instagram. Aktivitas Public Relations dengan memberikan staycation free kepada beberapa orang atau instansi yang terpilih (Influencer) serta melakukan cross market dengan beberapa pihak melalu Tag di media sosial. Alasan menggunakan media sosial sebagai strategi marketing karena media sosial memiliki kekuatan untuk mempengaruhi opini khalayak dan menimbulkan citra positif/negatif pihak-pihak yang diberitakannya dan peran media sosial yang besar bagi keberlangsungan suatu institusi.